CYBER SECURITY CHALLENGES IN THE AGE OF DIGITALISATION: HOW CAN COMPUTERS BE PROTECTED? - Loso Judijanto; Al-Amin (ADISAM Publisher, 2025)
In the era of growing digitalisation, cybersecurity challenges have become critical issues that require serious attention from individuals and organisations. Various types of cyber threats such as ransomware, phishing, and DDoS attacks are increasingly sophisticated and diverse, demanding a comprehensive and proactive approach to digital asset protection. Ensuring computers are protected requires a combination of up-to-date security technologies such as antivirus, firewalls, data encryption, and multifactor authentication, as well as strict security policy implementation and ongoing education. Success in meeting these challenges also depends on adaptability and rapid response to dynamic threats, with the development of effective emergency response plans. The right combination of technology, policy and operational preparedness will provide robust and responsive protection amidst the complexity of today's digital landscape.